2015
DOI: 10.1016/j.biopsycho.2015.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Preferential decoding of emotion from human non-linguistic vocalizations versus speech prosody

Abstract: This study used event-related brain potentials (ERPs) to compare the time course of emotion processing from non-linguistic vocalizations versus speech prosody, to test whether vocalizations are treated preferentially by the neurocognitive system. Participants passively listened to vocalizations or pseudo-utterances conveying anger, sadness, or happiness as the EEG was recorded. Simultaneous effects of vocal expression type and emotion were analyzed for three ERP components (N100, P200, Late Positive Component)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
134
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(163 citation statements)
references
References 90 publications
14
134
1
1
Order By: Relevance
“…The prosody of speech (discussed in the next section), consisting of pitch, loudness contour, and rhythm of speech articulation, evolves relatively slowly over suprasegmental speech intonations (>200 ms). The quality of non-speech vocalization (discussed in this section), consisting of timbre and abrupt, aperiodic spectral changes, emerges more rapidly (Pell et al, 2015), and has been shown to convey certain emotional categories (e.g., fear, disgust) potently (Banse and Scherer, 1996; Scott et al, 1997). Similar to emotional faces, emotional voices appear to confer perceptual advantages, as evidenced by improved memory for emotional over neutral nonspeech vocalizations (Armony et al, 2007) and priming effects across non-verbal vocalizations and faces or words conveying the same emotional category (Carroll and Young, 2005).…”
Section: Perception Of Emotional Non-verbal Vocalizationsmentioning
confidence: 99%
“…The prosody of speech (discussed in the next section), consisting of pitch, loudness contour, and rhythm of speech articulation, evolves relatively slowly over suprasegmental speech intonations (>200 ms). The quality of non-speech vocalization (discussed in this section), consisting of timbre and abrupt, aperiodic spectral changes, emerges more rapidly (Pell et al, 2015), and has been shown to convey certain emotional categories (e.g., fear, disgust) potently (Banse and Scherer, 1996; Scott et al, 1997). Similar to emotional faces, emotional voices appear to confer perceptual advantages, as evidenced by improved memory for emotional over neutral nonspeech vocalizations (Armony et al, 2007) and priming effects across non-verbal vocalizations and faces or words conveying the same emotional category (Carroll and Young, 2005).…”
Section: Perception Of Emotional Non-verbal Vocalizationsmentioning
confidence: 99%
“…Perhaps surprisingly, the amygdala is rarely implicated (Ethofer et al , 2007; Brück et al , 2011; Mothes-Lasch et al , 2011) unless more lenient statistical thresholds are used (Beaucousin et al , 2007; Fecteau et al , 2007). In the ERP, the LPP shows larger amplitudes for emotional as compared with neutral expressions (Pell et al , 2015; Pinheiro et al , 2016). Additionally, there are earlier emotion effects temporally overlapping with the FTPV.…”
Section: Introductionmentioning
confidence: 96%
“…A study compared the ERP responses toward the perception of three basic emotions (happiness, sadness, and anger) in vocalization vs. pseudo-speech (same as real-speech except the lexical-semantic contents were replaced by meaningless syllables [10,11]) in a task when listeners were presented with emotional vocal expressions followed by emotional and neutral faces and were asked to judge the emotionality of the face. Pell et al [11] showed that the vocalization and speech can be diferentiated very early at about 100 ms. Vocalization elicited a larger, earlier, and more diferentiated P200 between emotions, and a stronger and earlier late-positivity efect. These indings support a preferential decoding in the neurophysiological system of vocalization over speech-embedded emotions in the human voice.…”
Section: Neurophysiological Studies On Basic Vocal Emotion In Speech mentioning
confidence: 99%